Anisotropic distortions in Sb doped CePt4Ge12. Issue 1 (March 2015) - Bridges, F; Nast, P; Wilde, J; Keiber, T; Maple, M B; Huang, K; White, B D
Abstract: We investigated the local structure of the Sb doped skutterudite CePt4 Ge12- x Sb x using the Extended X-ray Absorption Fine Structure Technique (EXAFS). As the concentration of Sb is increased the disorder around Ce increases rapidly, and for x = 3, the peak for the nearest neighbor (Ce-Ge) is no longer observed. In contrast, for the Pt site, the disorder of the nearest neighbors is small even for x = 3. Thus the distortions are anisotropic and appear to be mainly in the plane of the Ce-Ge bonds and Ge4 rings. The increased disorder about Ce will decrease the lattice thermal conductivity at low temperatures, and likely is part of the reason for improved thermoelectric properties for the x = 1 sample.